DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN MOTIVASI BELAJAR PADA MAHASISWA - Yunita Fitria Rejeki; Shilviani Rahayu; Suparni Suparni (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2023)
Social support is one of the factors that influence students' learning motivation to achieve an achievement. Thus, learning motivation can be triggered by two different directions, namely from within and outside the individual or the surrounding environment that has similar goals. The purpose of this study was to determine the relationship between peer social support and learning motivation in level I engagement undergraduate students at STIKes Dharma Husada. This type of research is a quantitative correlation with a cross sectional research design. With the independent variable peer social support and the dependent variable learning motivation. Univariate using the frequency distribution and bivariate data analysis, using the Spearman rank correlation test to see the relationship between variables. The results of assistance and analysis of the relationship between peer social support and learning motivation in undergraduate students at level I engagement at STIKes Dharma Husada obtained the results of p-value (0.000) < É‘ (0.05) which means that there is a significant relationship between peer social support and motivation to study in level I fellowship undergraduate students at STIKes Dharma Husada. The results of this study are expected to be input for institutions in increasing understanding of the importance of peer social support and learning motivation in students and can help future researchers to study further about peer social support with student learning motivation by looking at the shortcomings in this study